Magnesium alloy surface rGO / Zn composite coating and preparation method and application thereof

By introducing a reduced graphene oxide interlayer rGO/Zn composite coating on the surface of magnesium alloy, the problem of insufficient adhesion of zinc coating was solved, significantly improving the corrosion resistance and biocompatibility of magnesium alloy, and meeting the long-term service requirements of magnesium alloy in body fluid environment.

CN121110140APending Publication Date: 2025-12-12CHONGQING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511283580.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-09
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

Existing zinc coatings on magnesium alloy surfaces have insufficient adhesion, unsatisfactory corrosion protection, and poor biocompatibility, making it difficult to meet the long-term service requirements in bodily fluid environments.

Method used

A reduced graphene oxide (rGO) interlayer is introduced on the surface of a magnesium alloy, and an rGO/Zn composite coating is formed by electrophoretic deposition. The barrier properties and interfacial bonding characteristics of rGO are used to improve the adhesion and stability of the zinc coating to the substrate, and the corrosion resistance and biocompatibility are improved by the outer zinc coating.

Benefits of technology

It significantly improves the adhesion and stability between the coating and the substrate, reduces the initial corrosion rate of magnesium alloys, enhances corrosion resistance and biocompatibility, imparts antibacterial properties, overcomes the shortcomings of a single zinc coating, and enhances protective performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121110140A_ABST
    Figure CN121110140A_ABST
Patent Text Reader

Abstract

The invention discloses a magnesium alloy surface rGO / Zn composite coating. The composite coating is composed of a compact and conductive reduced graphene oxide (rGO) layer and a uniform and compact zinc (Zn) layer. The invention further discloses a preparation method of the rGO / Zn composite coating on the surface of the magnesium alloy. The preparation method comprises the steps that S1, the surface of the magnesium alloy is pretreated; s2, preparing a graphene oxide (GO) coating through electrophoretic deposition; s3, performing vacuum thermal reduction on the GO coating to obtain an rGO coating; and S4, the zinc coating is further constructed on the surface of the rGO coating through electrophoretic deposition. The rGO intermediate layer not only improves the binding force and stability of the coating and a matrix, but also effectively reduces the initial corrosion rate of the magnesium alloy; and the outer zinc coating further improves the corrosion resistance and endows biocompatibility and antibacterial property. Compared with the prior art, the process is simple and convenient, the corrosion resistance of the prepared composite coating is remarkably improved, and the large-scale application prospect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of alloy surface modification technology, specifically relating to a magnesium alloy surface rGO / Zn composite coating, its preparation method, and its application. Background Technology

[0002] Magnesium and its alloys are considered to be a promising next-generation medical metal implant material due to their low density, high specific strength, elastic modulus close to that of human bone tissue, good biocompatibility, and biodegradability, especially in fracture fixation, cardiovascular stents, and tissue engineering. However, magnesium alloys corrode too rapidly in bodily fluids, typically undergoing significant degradation within weeks or even less after implantation. This leads to premature loss of the implant's mechanical properties, making it difficult to meet the mechanical support required for tissue healing. Furthermore, the rapid degradation releases hydrogen gas that can accumulate locally, potentially triggering alkalization and inflammatory reactions, thus severely limiting the clinical application of magnesium alloys.

[0003] Surface treatment is an effective method to improve the corrosion resistance, biocompatibility, and bioactivity of magnesium-based implants. Traditional surface modification methods mainly include anodic oxidation, micro-arc oxidation, chemical conversion coating, electroplating, and polymer coating. While these methods improve the corrosion resistance of magnesium alloys to some extent, they generally suffer from problems such as brittle films, microcracks, potential introduction of harmful ions, insufficient long-term stability, or poor adhesion to the substrate. In contrast, electrophoretic deposition (EPD) has advantages such as simple process, wide applicability, and the ability to obtain uniform coatings on complex morphological surfaces, and is therefore considered a promising surface modification technology.

[0004] Zinc, an essential trace element for the human body, has good biocompatibility and can promote bone tissue growth. Meanwhile, Zn... 2+ Zinc ions possess certain antibacterial properties. Furthermore, zinc can preferentially dissolve as a sacrificial anode in corrosive environments, effectively protecting the magnesium alloy substrate, thus making it a potential candidate for protective coatings. However, existing research and practical experience indicate that directly depositing zinc coatings on the highly reactive magnesium alloy substrate often results in insufficient adhesion between the coating and the substrate, easy peeling or cracking of the deposited layer, and defects in the passage of corrosive media leading to localized increased corrosion. This makes it difficult for the coating to achieve a durable and stable protective effect, and may even exacerbate localized corrosion. Therefore, relying solely on a single zinc coating is insufficient to meet the long-term service requirements of magnesium alloys in body fluid environments. Summary of the Invention

[0005] This invention aims to at least partially solve one of the technical problems in related technologies. Therefore, the main objective of this invention is to provide an rGO / Zn composite coating for magnesium alloy surfaces, which aims to overcome the shortcomings of existing electrophoretic deposited Zn coatings, such as insufficient adhesion, unsatisfactory corrosion protection, and poor biocompatibility.

[0006] The present invention also provides a method for preparing the rGO / Zn composite coating on the surface of the magnesium alloy, which achieves synergistic optimization of the coating structure by introducing a reduced graphene oxide (rGO) layer between the magnesium and its alloy and the zinc layer, thereby significantly improving corrosion resistance and stability.

[0007] The present invention also provides the application of the aforementioned rGO / Zn composite coating on the magnesium alloy surface in medical materials.

[0008] The objective of this invention is achieved through the following technical solution: A magnesium alloy surface rGO / Zn composite coating, wherein the magnesium and its alloy surface are provided with a reduced graphene oxide layer and a zinc layer from the inside out.

[0009] As part of the same inventive concept, this invention also provides a method for preparing the aforementioned rGO / Zn composite coating on the magnesium alloy surface, comprising the following steps: S1, GO electrophoretic deposition: In-situ surface modification of magnesium / magnesium alloy substrates was carried out by electrophoretic deposition technology to obtain GO coated samples; S2, Thermal reduction treatment: The GO coating sample from step S1 is placed in a vacuum furnace for thermal reduction treatment to obtain the rGO coating sample; S3, Zinc electrophoretic deposition: A Zn coating was constructed on the rGO coating sample obtained in S2 using electrophoretic deposition technology to obtain an rGO / Zn composite coating sample; S4. Post-treatment: After deposition, the sample is cleaned and dried to obtain the rGO / Zn composite coating on the magnesium alloy surface.

[0010] This invention uses a biodegradable magnesium alloy as a substrate and introduces a reduced graphene oxide (rGO) interlayer on the magnesium alloy surface via thermal reduction. Utilizing rGO's excellent barrier properties and interfacial bonding characteristics, the adhesion and stability of the zinc coating to the substrate are significantly improved. A zinc coating is then formed on the surface via electrophoretic deposition, resulting in an rGO / Zn biodegradable composite coating. The reduced graphene oxide coating not only improves the adhesion and stability between the coating and the substrate but also effectively reduces the initial corrosion rate of the magnesium alloy. The outer zinc coating further enhances corrosion resistance and imparts biocompatibility and antibacterial properties. This rGO / Zn composite coating structure combines the biocompatibility and sacrificial anode effects of zinc coatings while overcoming the shortcomings of directly deposited zinc coatings, significantly improving the protective performance and application potential of the coating.

[0011] In some specific embodiments, the oxide layer on the surface of the magnesium / magnesium alloy substrate is removed by mechanical or chemical methods before GO electrophoretic deposition.

[0012] Furthermore, the mechanical or chemical methods are as follows: the magnesium alloy substrate sample is polished with 400#, 800#, 1200# and 2000# SiC sandpaper in sequence until the surface of the magnesium alloy substrate sample is smooth, the magnesium alloy substrate sample is cleaned with anhydrous ethanol and dried for later use. In some specific embodiments, the in-situ surface modification of the magnesium alloy substrate by electrophoretic deposition technology in step S1 specifically includes: 1) Prepare the electrolyte solution by dissolving the electrolyte in anhydrous ethanol; 2) After the electrolyte is evenly dispersed, the magnesium / magnesium alloy substrate is subjected to electrophoretic deposition to obtain a GO coating sample.

[0013] In some specific embodiments, the electrolyte comprises the following components and proportions of raw materials: 8-16 mg graphene oxide, 45-70 mg zinc nitrate, 45-60 mg zinc acetate, and 150-450 ml anhydrous ethanol.

[0014] In some specific embodiments, the anode of the electrophoretic deposition process is a platinum sheet, the cathode is the magnesium / magnesium alloy substrate, the voltage is 60-100V, the electrode spacing is 1-3cm, and the electrophoretic deposition time is 4-6min.

[0015] In some specific embodiments, the process conditions for the thermal reduction treatment in step S2 are as follows: the temperature is increased at a rate of 4-8℃ / min, and then held at 180-250℃ for 1-2 h to transform the GO layer into an rGO intermediate layer with good conductivity and barrier properties.

[0016] In some specific embodiments, step S3 uses electrophoretic deposition to construct a Zn coating on the rGO-coated sample, specifically as follows: 1) Preparation of electrolyte solution: Dissolve zinc sulfate heptahydrate and sodium citrate in deionized water, adjust the Zn ion concentration to 0.05-0.2 mol / L, and adjust the pH to 4.0-5.0 with HCl; 2) Preparation of Zn coating: Using the rGO coating sample as the cathode and the titanium sheet as the anode, a dense zinc coating was obtained by deposition at a voltage of 5-30V for 5-30min, thus obtaining the rGO / Zn composite coating sample.

[0017] In some specific embodiments, the drying process parameters in step S4 are: drying at a temperature of 40-80℃ for 0.5-1h.

[0018] As part of the same inventive concept, this application also provides the application of the aforementioned rGO / Zn composite coating on the magnesium alloy surface in medical materials.

[0019] Compared with the prior art, the present invention has at least the following advantages: 1. The preparation method of this application, through vacuum thermal reduction, effectively improves the interfacial bonding between the magnesium alloy substrate and the outer zinc coating by preparing the rGO intermediate layer, thus preventing coating peeling.

[0020] 2. In the composite coating of the present invention, the rGO layer provides a barrier to prevent the penetration of corrosive media, and the outer zinc coating acts as a sacrificial anode to further delay the corrosion of the substrate. The two layers work synergistically to significantly reduce the corrosion rate; and both rGO and Zn are biosafe materials, wherein Zn 2+ Ion release has the effects of promoting bone formation and antibacterial activity, and has a high overall safety profile.

[0021] 3. The preparation method of the present invention, which combines electrophoretic deposition with thermal reduction, is mild, simple to operate, low in cost, and suitable for large-scale promotion. Attached Figure Description

[0022] To more clearly illustrate the specific embodiments of the present invention, the accompanying drawings used in the description of the specific embodiments or the prior art will be briefly introduced below.

[0023] Figure 1 This is a surface morphology image of the coating sample (rGO / Zn-0.1 / 10) prepared in Example 1 of this invention; Figure 2 The image shows the surface morphology of the coating sample (rGO / Zn-0.1 / 20) prepared in Example 2 of this invention. Figure 3 The image shows the surface morphology of the coating sample (rGO / Zn-0.2 / 10) prepared in Example 3 of this invention. Figure 4 The image shows the surface morphology of the coating sample (rGO / Zn-0.2 / 20) prepared in Example 4 of this invention. Figure 5 This is an EDS spot scan image of the coating sample prepared in Example 2 of this invention; Figure 6 The thickness scanning morphology and statistical graphs of the coatings in Examples 1, 2, 3 and 4 are shown. Figure 7 The diagrams show the bonding strength tests of SM, rGO (Example 1), and Examples 1, 2, 3, and 4; where (a), (b), (c), (d), and (e) represent samples rGO, GO / Zn-0.1 / 10, rGO / Zn-0.1 / 20, rGO / Zn-0.2 / 10, and rGO / Zn-0.2 / 20, respectively. Figure 8 The results of hydrogen evolution experiments for SM, rGO (Example 1), and Examples 1, 2, 3, and 4 are shown. Figure 9 Annual corrosion rate diagrams obtained from hydrogen evolution experiments of SM, rGO (Example 1), and Examples 1, 2, 3, and 4; Figure 10 The results are for pH change experiments of SM, rGO (Example 1) and Examples 1, 2, 3 and 4. Detailed Implementation

[0024] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. The following embodiments are merely descriptive and not limiting, and should not be construed as limiting the scope of protection of the present invention.

[0025] When a quantity, concentration, or other value or parameter is described as a range, preferred range, or preferred upper and lower limits, it should be understood that it is equivalent to specifically disclosing any range by combining any pair of upper or preferred values ​​with any lower or preferred values, regardless of whether the range is specifically disclosed. Unless otherwise stated, the numerical range values ​​listed herein include the endpoints of the range and all integers and fractions within that range.

[0026] Unless otherwise stated, all percentages, parts, ratios, etc. in this document are by weight.

[0027] The materials, methods, and embodiments described herein are exemplary and should not be construed as limiting unless otherwise stated.

[0028] Example 1 This embodiment provides a method for preparing an rGO / Zn composite coating on a magnesium alloy surface, comprising the following steps: S1. Matrix pretreatment: The Mg-Sr-Mn magnesium alloy substrate sample was polished with 400#, 800#, 1200# and 2000# SiC sandpaper in sequence until the surface of the Mg-Sr-Mn magnesium alloy substrate sample was smooth. The magnesium alloy substrate sample was cleaned with anhydrous ethanol and dried for later use to obtain the pretreated Mg-Sr-Mn magnesium alloy matrix (abbreviated as SM). S2, GO electrophoretic deposition: The Mg-Sr-Mn magnesium alloy substrate was immersed in an electrolyte (the electrolyte includes the following components and proportions of raw materials: 12mg graphene oxide, 58mg zinc nitrate, 52mg zinc acetate and 250ml anhydrous ethanol) for electrophoretic deposition. Specifically, the electrophoretic deposition was carried out with a platinum sheet as the anode, the Mg-Sr-Mn magnesium alloy substrate as the cathode, the voltage as 80V, the electrode spacing as 2cm, and the electrophoretic deposition for 6min to obtain a GO coated sample. S3. Thermal reduction treatment: The GO coating sample from step S2 is placed in a vacuum furnace and heated at a rate of 5℃ / min until it reaches 200℃ and is held at that temperature for 1.5h to obtain a reduced graphene oxide (rGO) coating sample. S4. Zinc electrophoretic deposition: The rGO coating sample described in S3 was immersed in an electrolyte solution (the electrolyte solution was prepared by dissolving 7.19 g of zinc sulfate heptahydrate and 3.2 g of sodium citrate in 250 ml of deionized water, adjusting the Zn ion concentration to 0.1 mol / L, and adjusting the pH to 4.6-4.7 with HCl). Using the rGO coating sample as the cathode and the titanium sheet as the anode, deposition was carried out at 10 V for 10 min to obtain a dense zinc coating, thus obtaining the reduced graphene oxide / zinc (rGO / Zn) composite coating sample. S5. Post-treatment: After deposition, the sample is washed with deionized water and dried at 55℃ for 0.5h to obtain a firmly bonded, dense and uniform rGO / Zn composite coating, namely the rGO / Zn composite coating on the magnesium alloy surface (abbreviated as rGO / Zn-0.1 / 10).

[0029] Example 2 This embodiment provides a method for preparing an rGO / Zn composite coating on a magnesium alloy surface, comprising the following steps: S1. Substrate pretreatment: The Mg-Sr-Mn magnesium alloy substrate sample was polished with 400#, 800#, 1200# and 2000# SiC sandpaper in sequence until the surface of the Mg-Sr-Mn magnesium alloy substrate sample was smooth. The magnesium alloy substrate sample was cleaned with anhydrous ethanol and dried for later use. S2, GO electrophoretic deposition: The Mg-Sr-Mn magnesium alloy substrate was immersed in an electrolyte (the electrolyte includes the following components and proportions of raw materials: 12mg graphene oxide, 58mg zinc nitrate, 52mg zinc acetate and 250ml anhydrous ethanol) for electrophoretic deposition. Specifically, the electrophoretic deposition was carried out with a platinum sheet as the anode, the Mg-Sr-Mn magnesium alloy substrate as the cathode, the voltage as 80V, the electrode spacing as 2cm, and the electrophoretic deposition for 6min to obtain a GO coated sample. S3. Thermal reduction treatment: The GO coating sample from step S2 is placed in a vacuum furnace and heated at a rate of 5℃ / min until it reaches 200℃ and is held at that temperature for 1.5h to obtain a reduced graphene oxide (rGO) coating sample. S4. Zinc electrophoretic deposition: The rGO coating sample described in S3 was immersed in an electrolyte solution (the electrolyte solution was prepared by dissolving 7.19 g of zinc sulfate heptahydrate and 3.2 g of sodium citrate in 250 ml of deionized water, adjusting the Zn ion concentration to 0.1 mol / L, and adjusting the pH to 4.6-4.7 with HCl). The rGO coating sample was used as the cathode and the titanium sheet was used as the anode. Deposition was carried out at 10 V for 20 min to obtain a dense zinc coating, thus obtaining the reduced graphene oxide / zinc (rGO / Zn) composite coating sample. S5. Post-treatment: After deposition, the sample is washed with deionized water and dried at 55℃ for 0.5h to obtain a firmly bonded, dense and uniform rGO / Zn composite coating, namely the rGO / Zn composite coating on the magnesium alloy surface (abbreviated as rGO / Zn-0.1 / 20).

[0030] Example 3 This embodiment provides a method for preparing an rGO / Zn composite coating on a magnesium alloy surface, comprising the following steps: S1. Substrate pretreatment: The Mg-Sr-Mn magnesium alloy substrate sample was polished with 400#, 800#, 1200# and 2000# SiC sandpaper in sequence until the surface of the Mg-Sr-Mn magnesium alloy substrate sample was smooth. The magnesium alloy substrate sample was cleaned with anhydrous ethanol and dried for later use. S2, GO electrophoretic deposition: The Mg-Sr-Mn magnesium alloy substrate was immersed in an electrolyte (the electrolyte includes the following components and proportions of raw materials: 12mg graphene oxide, 58mg zinc nitrate, 52mg zinc acetate and 250ml anhydrous ethanol) for electrophoretic deposition. Specifically, the electrophoretic deposition was carried out with a platinum sheet as the anode, the Mg-Sr-Mn magnesium alloy substrate as the cathode, the voltage as 80V, the electrode spacing as 2cm, and the electrophoretic deposition for 6min to obtain a GO coated sample. S3. Thermal reduction treatment: The GO coating sample from step S2 is placed in a vacuum furnace and heated at a rate of 5℃ / min until it reaches 200℃ and is held at that temperature for 1.5h to obtain a reduced graphene oxide (rGO) coating sample. S4. Zinc electrophoretic deposition: The rGO coating sample described in S3 was immersed in an electrolyte solution (the electrolyte solution was prepared by dissolving 14.38 g of zinc sulfate heptahydrate and 6.4 g of sodium citrate in 250 ml of deionized water, adjusting the Zn ion concentration to 0.2 mol / L, and adjusting the pH to 4.6-4.7 with HCl). Using the rGO coating sample as the cathode and the titanium sheet as the anode, deposition was carried out at 10 V for 10 min to obtain a dense zinc coating, thus obtaining the reduced graphene oxide / zinc (rGO / Zn) composite coating sample. S5. Post-treatment: After deposition, the sample is washed with deionized water and dried at 55℃ for 0.5h to obtain a firmly bonded, dense and uniform rGO / Zn composite coating, namely the rGO / Zn composite coating on the magnesium alloy surface (abbreviated as rGO / Zn-0.2 / 10).

[0031] Example 4 This embodiment provides a method for preparing an rGO / Zn composite coating on a magnesium alloy surface, comprising the following steps: S1. Substrate pretreatment: The Mg-Sr-Mn magnesium alloy substrate sample was polished with 400#, 800#, 1200# and 2000# SiC sandpaper in sequence until the surface of the Mg-Sr-Mn magnesium alloy substrate sample was smooth. The magnesium alloy substrate sample was cleaned with anhydrous ethanol and dried for later use. S2, GO electrophoretic deposition: The Mg-Sr-Mn magnesium alloy substrate was immersed in an electrolyte (the electrolyte includes the following components and proportions of raw materials: 12mg graphene oxide, 58mg zinc nitrate, 52mg zinc acetate and 250ml anhydrous ethanol) for electrophoretic deposition. Specifically, the electrophoretic deposition was carried out with a platinum sheet as the anode, the Mg-Sr-Mn magnesium alloy substrate as the cathode, the voltage as 80V, the electrode spacing as 2cm, and the electrophoretic deposition for 6min to obtain a GO coated sample. S3. Thermal reduction treatment: The GO coating sample from step S2 is placed in a vacuum furnace and heated at a rate of 5℃ / min until it reaches 200℃ and is held at that temperature for 1.5h to obtain a reduced graphene oxide (rGO) coating sample. S4. Zinc electrophoretic deposition: The rGO coating sample described in S3 was immersed in an electrolyte solution (the electrolyte solution was prepared by dissolving 14.38 g of zinc sulfate heptahydrate and 6.4 g of sodium citrate in 250 ml of deionized water, adjusting the Zn ion concentration to 0.2 mol / L, and adjusting the pH to 4.6-4.7 with HCl). Using the rGO coating sample as the cathode and the titanium sheet as the anode, deposition was carried out at 10 V for 20 min to obtain a dense zinc coating, thus obtaining the reduced graphene oxide / zinc (rGO / Zn) composite coating sample. S5. Post-treatment: After deposition, the sample is washed with deionized water and dried at 55℃ for 0.5h to obtain a firmly bonded, dense and uniform rGO / Zn composite coating, namely the rGO / Zn composite coating on the magnesium alloy surface (abbreviated as rGO / Zn-0.2 / 20).

[0032] Performance characterization: The present invention conducts performance tests on the rGO / Zn composite coatings on the magnesium alloy surface prepared in Examples 1-4, specifically as follows: 1) Microscopic morphology This application performs electron microscopy scanning on the surface of the rGO / Zn composite coating on the magnesium alloy prepared in Examples 1-4, and the microstructure images are as follows: Figure 1 , Figure 2 , Figure 3 and Figure 4 As shown in the figure, a Zn coating was formed on the surface of all four groups of samples (Examples 1-4), which consisted of needle-like and granular structures. However, the uniformity of the coatings in Examples 1, 3, and 4 was relatively poor, while Example 2 had a uniform and dense microstructure.

[0033] 2) EDS elemental identification This application uses Example 2 as an example to perform EDS spot scanning on the surface of the rGO / Zn composite coating on the magnesium alloy surface prepared in Example 2. The results are as follows: Figure 5 As shown in the figure, the needle-like and granular substances on the surface of the magnesium alloy in this application are Zn coatings.

[0034] 3) Coating thickness test This application tests the thickness of the rGO / Zn composite coating on the magnesium alloy surface prepared in Examples 1-4, and the results are as follows: Figure 6 As shown, where Figure 6 (a), (b), (c), and (d) in the figures are the detection results of Examples 1, 2, 3, and 4, respectively, which are rGO / Zn-0.1 / 10, rGO / Zn-0.1 / 20, rGO / Zn-0.2 / 10, and rGO / Zn-0.2 / 20.

[0035] The upper part of the image shows the embedded resin, and the lower part shows the magnesium alloy substrate; the zinc coating thicknesses of the samples corresponding to Examples 1-4 are 11.375 μm, 14.231 μm, 15.246 μm, and 21.208 μm, respectively. Figure 6 It is evident that the thickness of the zinc coating increases with increasing deposition time and zinc ion concentration in the solution. This indicates that appropriately increasing the deposition time or raising the zinc ion concentration during galvanizing can increase the coating thickness, which may improve its corrosion resistance and application potential.

[0036] 4) Coating adhesion This application tests the adhesion of the rGO / Zn composite coatings on the magnesium alloy surface prepared in Examples 1-4. Specifically: Test Method: A 1mm square grid was cut into the coating using a cross-cutting tool. 3M Scotch 610 tape was then applied to the coating and pressed firmly. The tape was then peeled off at a uniform speed from a 60° angle to the horizontal. The peeling of the coating was observed, and the adhesion was rated. The test results were divided into five levels: Level 0 (best), indicating no peeling at the grid edges, completely smooth cut edges, and no peeling; Level 1, peeling area ≤ 5%; Level 2, peeling area 5%~15%; Level 3, peeling area 15%~35%; Level 4, peeling area 35%~65%; Level 5 (worst), peeling area ≥ 65%, indicating extremely poor coating adhesion, easy separation from the substrate, and essentially loss of protective ability. Test samples: rGO / Zn composite coatings on magnesium alloy surfaces prepared in Examples 1-4, and reduced graphene oxide (rGO) coating samples prepared in step S3 of Example 1; The results are as follows Figure 7 As shown in Table 1: Table 1. Detachment area and rating of each sample in Examples 1-4 in Figure 7 (a), (b), (c), (d), and (e) represent samples rGO, GO / Zn-0.1 / 10, rGO / Zn-0.1 / 20, rGO / Zn-0.2 / 10, and rGO / Zn-0.2 / 20, respectively. (The last part, "through...", appears to be an incomplete sentence or fragment.) Figure 7 As shown in Table 1, except for Example 1, the peeling area of ​​all coatings was below 15%, and the adhesion rating was above 2, demonstrating good adhesion strength. Composite coatings also contribute to improving the adhesion strength of the coatings. The adhesion strength of the five samples was in the following order: rGO / Zn-0.1 / 20 > rGO / Zn-0.2 / 10 > rGO > rGO / Zn-0.2 / 20 > rGO / Zn-0.1 / 10. This indicates that when the zinc ion concentration is the same and the concentration is low, the longer the deposition time, the better the film adhesion and the stronger the adhesion. However, when the zinc ion concentration is high, the longer the deposition time, the lower the film adhesion, but the effect is still stronger than that of low concentration and low deposition time. At the same time, when the deposition time is the same, excessively high zinc ion concentration will also reduce the adhesion strength.

[0037] 5) Hydrogen evolution experiment This application tests the corrosion resistance of the rGO / Zn composite coatings on the magnesium alloy surface prepared in Examples 1-4, specifically: Magnesium alloys produce hydrogen gas when they degrade in the human body. Therefore, the corrosion resistance of a material can be assessed by detecting the amount of hydrogen produced. A higher amount of hydrogen released per unit area means a faster corrosion rate. Figure 8The hydrogen evolution results are obtained by immersing the pretreated Mg-Sr-Mn magnesium alloy substrate (SM) from Example 1, the reduced graphene oxide (rGO) prepared in step S3, and the samples from Examples 1 (rGO / Zn-0.1 / 10), 2 (rGO / Zn-0.1 / 20), 3 (rGO / Zn-0.2 / 10), and 4 (rGO / Zn-0.2 / 20) in simulated body fluid for 7 days. As can be seen from the figure, all samples produced a relatively large amount of hydrogen gas before 24 hours, after which the hydrogen release rate gradually decreased and eventually stabilized. Compared to SM and rGO, the composite coating with deposited Zn exhibited a lower hydrogen evolution rate. The hydrogen evolution per unit area after 7 days of immersion for SM, rGO, and Examples 1, 2, 3, and 4 was 4.3279 ml / cm². 2 3.68687 ml / cm 2 3.05499 / cm 2 0.95468 ml / cm 2 1.4002 ml / cm 2 and 1.65479 ml / cm 2 Therefore, the corrosion resistance of the six samples is in the order of rGO / Zn-0.1 / 20 > rGO / Zn-0.2 / 10 > rGO > rGO / Zn-0.2 / 20 > rGO / Zn-0.1 / 10 > rGO > SM. Figure 1 , 2 Comparing 3, 4, and 7, it can be found that the strength of the coating's corrosion resistance is closely related to the coating's bonding strength and the uniformity of its application.

[0038] in addition, Figure 9 The annual corrosion rate diagrams for six materials were obtained based on hydrogen evolution experiments. The annual corrosion rate of the SM alloy was 1.40 mm / y. The single-layer rGO coating obtained through electrophoretic deposition and vacuum thermal reduction slightly reduced the annual corrosion rate of the alloy (1.18 mm / y). However, this still does not meet the annual corrosion rate requirements for medical implants (<0.5 mm / y). However, the annual corrosion degradation rate of the magnesium alloy with the deposited rGO / Zn composite coating decreased significantly. The annual corrosion rates of Examples 1, 2, 3, and 4 were 0.98 mm / y, 0.31 mm / y, 0.45 mm / y, and 0.53 mm / y, respectively. In particular, Examples 2 and 3 met the corrosion resistance requirements for medical implants, demonstrating extremely high application value. Simultaneously, excessively high or low deposition times and zinc ion concentrations will reduce the corrosion resistance of the rGO / Zn composite coating.

[0039] 6) pH test This application uses pH testing to further analyze the corrosion resistance of the coated samples. The results are as follows: Figure 10As shown, the pH changes of the magnesium alloy substrate sample and all coated samples after immersion in m-SBF for 7 days are presented. Consistent with the hydrogen evolution experiment results, the pH value of the solution for all samples rose sharply in the initial stage of immersion, but the rate of increase gradually slowed down after 24 hours. After immersion for 168 hours, the pH value of the solution for all alloys remained below 8.6; while the rGO / Zn composite coating showed an even lower pH value, remaining below 8.3. The closer the pH of the solution is to neutral, the better it is for preventing inflammation near medical implants. This proves that the rGO / Zn composite coating prepared by electrophoretic deposition significantly enhances the corrosion resistance of the alloy and provides better protection against corrosion of magnesium alloys in the human body environment. Considering the coating morphology, adhesion, and corrosion resistance test results, Example 2 (rGO / Zn-0.1 / 20) exhibits the best comprehensive performance within the parameter range provided by this invention.

[0040] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be covered within the scope of the claims and specification of the present invention.

Claims

1. A rGO / Zn composite coating on a magnesium alloy surface, characterized in that, The magnesium and its alloys have a reduced graphene oxide layer and a zinc layer arranged sequentially from the inside out on their surfaces.

2. The method for preparing the rGO / Zn composite coating on the magnesium alloy surface according to claim 1, characterized in that, Includes the following steps: S1, GO electrophoretic deposition: In-situ surface modification of magnesium / magnesium alloy substrates was carried out by electrophoretic deposition technology to obtain GO coated samples; S2, Thermal reduction treatment: The GO coating sample from step S1 is placed in a vacuum furnace for thermal reduction treatment to obtain the rGO coating sample; S3, Zinc electrophoretic deposition: A Zn coating was constructed on the rGO coating sample obtained in S2 using electrophoretic deposition technology to obtain an rGO / Zn composite coating sample; S4. Post-treatment: After deposition, the sample is cleaned and dried to obtain the rGO / Zn composite coating on the magnesium alloy surface.

3. The method for preparing the rGO / Zn composite coating on the magnesium alloy surface according to claim 2, characterized in that, It also includes removing the oxide layer on the surface of the magnesium / magnesium alloy substrate by mechanical or chemical methods before performing GO electrophoretic deposition on the magnesium / magnesium alloy substrate.

4. The method for preparing the rGO / Zn composite coating on the magnesium alloy surface according to claim 3, characterized in that, The in-situ surface modification of the magnesium alloy substrate by electrophoretic deposition technology described in step S1 specifically includes: 1) Prepare the electrolyte solution by dissolving the electrolyte in anhydrous ethanol; 2) After the electrolyte is evenly dispersed, the magnesium / magnesium alloy substrate is subjected to electrophoretic deposition to obtain a GO coating sample.

5. The method for preparing the rGO / Zn composite coating on the magnesium alloy surface according to claim 4, characterized in that, The electrolyte comprises the following components and proportions of raw materials: 8-16 mg graphene oxide, 45-70 mg zinc nitrate, 45-60 mg zinc acetate, and 150-450 ml anhydrous ethanol.

6. The method for preparing the rGO / Zn composite coating on the magnesium alloy surface according to claim 4, characterized in that, The anode for the electrophoretic deposition process is a platinum sheet, the cathode is the magnesium / magnesium alloy substrate, the voltage is 60-100V, the electrode spacing is 1-3cm, and the electrophoretic deposition time is 4-6min.

7. The method for preparing the rGO / Zn composite coating on the magnesium alloy surface according to claim 2, characterized in that, The process conditions for the thermal reduction treatment in step S2 are as follows: the temperature is increased at a rate of 4-8℃ / min, and then held at 180-250℃ for 1-2 hours.

8. The method for preparing the rGO / Zn composite coating on the magnesium alloy surface according to claim 2, characterized in that, In step S3, an electrophoretic deposition technique is used to construct a Zn coating on the rGO-coated sample, specifically as follows: 1) Preparation of electrolyte solution: Dissolve zinc sulfate heptahydrate and sodium citrate in deionized water, adjust the Zn ion concentration to 0.05-0.2 mol / L, and adjust the pH to 4.0-5.0 with HCl; 2) Preparation of Zn coating: Using the rGO coating sample as the cathode and the titanium sheet as the anode, a dense zinc coating was obtained by deposition at a voltage of 5-30V for 5-30 min, thus obtaining the rGO / Zn composite coating sample.

9. The method for preparing the rGO / Zn composite coating on the magnesium alloy surface according to claim 8, characterized in that, The drying process parameters in step S4 are: drying at a temperature of 40-80℃ for 0.5-1h.

10. The application of the rGO / Zn composite coating on the magnesium alloy surface according to claim 1 or the rGO / Zn composite coating on the magnesium alloy surface obtained by the preparation method according to any one of claims 2-9 in medical materials.